Sugar-Free Herbal Beverage Preferences: Customer Clustering Insights: Preferensi Minuman Herbal Bebas Gula: Wawasan Pengelompokan Pelanggan - Sudaryono, Hasna Nadiyah Banafsaj; Widyastuti, Hardiana; Sembiring, Indra Refipal; Andrianto, Mokhamad Syaefudin (Universitas Muhammadiyah Sidoarjo, 2024)
Amidst the increased demand for public health products caused by the COVID-19 epidemic, Indonesia's herbal business has recognized opportunity for expansion, particularly in the area of sugar-free instant herbal beverages. The purpose of this study is to define customer profiles and identify the factors impacting customers' willingness to pay for such products using a dual technique of cluster analysis and Structural Equation Modeling - Partial Least Squares (SEM-PLS). The study identifies three unique client groups: teen students (Cluster 1), early adult workers (Cluster 2), and late adult workers (Cluster 3). Income, health consciousness, product quality, and price are factors that have a favorable and significant impact on willingness to pay across all clusters. Notably, in Cluster 3, willingness to pay is more influenced by product quality, health consciousness, and price. These findings are useful for the Indonesian herbal business, as they will guide targeted marketing tactics and product development efforts to efficiently serve to varied consumer demographics.